ANALISIS TINGKAT KESULITAN (DIFFICULTY LEVEL) SOAL PADA BUKU SEJARAH KEBUDAYAAN ISLAM: KELAS 8 KURIKULUM 2013 - R. Ahmad Nur Kholis (Jurnal Penelitian Ilmiah INTAJ, 2017)
This study aims at describing the difficulty level of task items presented in chapter 1 and 2 in a book titled “Buku Guru Kurikulum 13 Mata Pelajaran Sejarah Kebudayaan Islam (SKI) Kelas 8”. This book is published by the Ministry of Religion Affair in 2015. The major data source analyzed in this study is the test result done by the eighth graders of MTs Nahdlatul Ulama Karangploso. The subject of this study is the task items contained in the topics about (1) the footsteps of Abbasite Dynasty, and (2) the Brilliance of Islamic Scholars in the Era of Abbasite Dynasty. Two kinds of analysis technique are employed in this study namely (1) Descriptive Statistic Analysis, also called Social Statistics, and (2) Proportion of correct. The result of the study shows that task items on both discussions in the book are 100% in difficulty level. Keywords: Difficulty Level, SKI Subject